EU’s palm oil challenge : how should Singapore respond - Ng, Jefferson Jin Chuan (2019)
Palm oil, a major commodity crop in the region, is likely to be phased out in the EU by 2030. Given the potential regional and transboundary implications, a Singapore-centric perspective can be helpful.